Oxidative damage in immunoglobulin light chain and transthyretin cardiac amyloidosis - a closer look - Elena Cavallone; Amir Hassan Mousavi; Carloalberto Biolé; Giulia Nangeroni; Alessandra Chinaglia; Matteo Bianco (Bioscientifica, 2024)
Heart failure is a progressive disease, representing a growing cause of morbidity, hospitalization, and mortality. An increasingly common type of heart failure with preserved ejection fraction (HFpEF) is an immunoglobulin light chain and transthyretin cardiac amyloidosis, in the pathophysiology of which oxidative damage appears to exert a strong impact. Reactive oxygen and nitrogen species have physiological signaling functions, but their overaccumulation, as in cardiac amyloidosis, leads to cardiomyocyte damage and apoptosis, and to cardiac hypertrophy and fibrosis. Moreover, such pathological processes worsen the redox damage with the perpetuation of an inflammatory state, in a vicious cycle. Here, the role of oxidative damage in the transthyretin and immunoglobulin light chain cardiac amyloidosis, the underlying pathogenic mechanisms, the therapeutic implications, and possible future strategies are reviewed.